Management practices and use of natural resources in the microregion of abejones, Oaxaca. - Bautista Vargas, Aldo; Castañeda Hidalgo, Ernesto; Santiago Martínez, Gisela Margarita; Pérez León, María Isabel; Juárez Sánchez, José Pedro; Lozano Trejo, Salvador (Agricultura, Sociedad y Desarrollo, 2022)
Indigenous communities conserve their local practices around natural resources, which contribute to the conservation of nature and the satisfaction of their dietary and sociocultural needs. The objective of the study was to analyze the practices of exploitation and management of natural resources in indigenous spaces of Oaxaca. The ethnoecological method was used: the structured interview and field visits. It was found that interview respondents implemented different types of agricultural practices, with the following standing out: sowing of associated or interspersed crops, construction of retention walls (bordos), and terraces and leveling. Soil management was carried out in a differentiated way; in two sites they use manure from backyard animals and in another community they use domestic waste. The water management practices were different per community and were subject to their culture; the management of irrigation water by gravity stood out, and to a lesser extent the harvest of rainwater. The harvest of plants, fungi and the exploitation of wild animals were also frequent. Rituals are still practiced that are devoted to the soil, to a lesser extent to water, to the mountain and to animals. It is concluded that the communities of study conserve their practices that were developed locally.